Composite diaphragm as well as preparation method and application thereof

By using a functional coating composed of two-dimensional sheet material and a lithium polydopamine salt in the lithium-ion battery separator, the problem of large-particle-size transition metal passing through the battery separator during the charge and discharge cycle is solved, and the separator strength and conductivity are achieved, the service life of the battery is extended, and the cycle stability and safety performance of the battery is improved.

CN119651061APending Publication Date: 2025-03-18NINGDE ZHUOGAO NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411830679.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During the charging and discharging cycle of the separator of existing lithium-ion batteries, large-particle transition metals such as Mn are prone to pass through the separator, resulting in direct contact between positive and negative electrode active materials and dissipation in the electrolyte, affecting the cycle stability and safety performance of the battery.

Method used

A composite separator is adopted, which includes a first substrate layer, a functional coating and a second substrate layer. The functional coating consists of a two-dimensional sheet material and a lithium polydopamine salt. The two-dimensional sheet material forms a network structure through hydrogen bonding, enhances the overall strength of the separator, and blocks large-particle-size transition metal by regulating the sheet spacing.

Benefits of technology

It improves the overall strength and conductivity of the composite separator, extends the service life, effectively blocks the passage of large-particle transition metals such as Mn, reduces direct contact with positive and negative electrode active materials and the risk of dissipation in the electrolyte, and improves the cycle stability and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119651061A_ABST
    Figure CN119651061A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a composite diaphragm as well as a preparation method and application thereof. The composite diaphragm comprises a first base material layer, a functional coating and a second base material layer, and the functional coating is located between the first base material layer and the second base material layer; the functional coating comprises a two-dimensional lamellar material and a polydopamine lithium salt. In the composite diaphragm, the functional coating is formed by stacking two-dimensional lamellar materials, and the distance between lamellar layers is regulated and controlled by lithium ions doped between the lamellar layers; the two-dimensional lamellar material forms a firm network structure through hydrogen-bond interaction, so that the overall strength of the composite diaphragm is enhanced; in the charge-discharge cycle process, the distance between the lamellas can effectively block Mn and other large-particle-size transition metals; and the middle functional coating is fixed by the substrate base materials on the two sides, so that the middle functional coating is prevented from being in direct contact with positive and negative active materials, and the risk that the middle functional coating escapes into electrolyte is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a composite diaphragm and a preparation method and application thereof. Background Art

[0002] As an important component of lithium batteries, the diaphragm plays the role of isolating the positive and negative electrodes at the battery end, so the performance of the diaphragm affects the overall performance of the battery. With the development of technology, the safety performance of batteries has received more and more attention, and the control of the puncture strength of the diaphragm has become more stringent. However, due to imperfect parameters or processes in the diaphragm production process, diaphragms that do not meet the puncture strength requirements are treated as abnormal products or waste, thus wasting a lot of resources.

[0003] In addition, during the charge and discharge cycle, lithium-ion batteries (LIBs) containing lithium-rich manganese-based positive electrode materials will experience significant capacity decay. Especially under high temperature conditions, Mn ions will quickly detach from the positive electrode material, pass through the diaphragm and deposit on the negative electrode, continuously destroying the solid electrolyte interface (SEI) and the consumption of Li ions. In existing composite diaphragms, the coating on the side of the substrate has the risk of falling off and escaping into the electrolyte, which in turn affects the cycle stability and safety performance of the battery.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One object of the present invention is to provide a composite diaphragm with high overall strength, which can effectively block large-particle transition metals such as Mn during the charge and discharge cycle, thereby avoiding direct contact with positive and negative electrode active materials and reducing the risk of escaping into the electrolyte.

[0006] Another object of the present invention is to provide a method for preparing a composite diaphragm, which is simple and easy to implement. The obtained composite diaphragm has good interlayer adhesion, high needle puncture strength, high ion conductivity, long service life, can delay the escape of the intermediate coating, and block transition metals such as Mn.

[0007] Another object of the present invention is to provide a battery.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] A composite diaphragm comprises a first substrate layer, a functional coating and a second substrate layer, wherein the functional coating is located between the first substrate layer and the second substrate layer; the functional coating comprises a two-dimensional sheet material and polydopamine lithium salt.

[0010] In some embodiments, along the thickness direction of the functional coating, the two-dimensional sheet material is in a stacked form.

[0011] In some embodiments, along the thickness direction of the functional coating, the spacing d between any adjacent two-dimensional sheet materials satisfies: 0.7 nm≤d≤1.4 nm.

[0012] In some embodiments, in the functional coating, the mass content A of the two-dimensional sheet material satisfies: A≥85%, and the mass content B of the polydopamine lithium salt satisfies: B≥3%.

[0013] In some embodiments, the two-dimensional sheet material includes at least one of graphene oxide, graphene, amino-modified graphene oxide, Mxene and molybdenum disulfide.

[0014] In some embodiments, the two-dimensional sheet material has a length of 0.1 to 5 μm.

[0015] In some embodiments, the functional coating has a thickness of 0.4 to 10 μm.

[0016] In some implementations, the functional coating further includes a thickener, and the mass content C of the thickener satisfies: C ≥ 0.3%, and A + B + C = 100%.

[0017] In some embodiments, the functional coating further includes a thickener, and the thickener includes at least one of carboxymethyl cellulose, carboxyethyl cellulose, guar gum, polyethylene oxide, pinene alcohol, polyvinyl alcohol, polyacrylic acid and polyurethane.

[0018] In some implementations, the composite membrane has a needle puncture strength of 350 to 900 gf, and the functional coating has a needle puncture strength of 60 to 300 gf.

[0019] In some embodiments, the bonding strength between the first substrate layer and the second substrate layer is greater than 10 N / m.

[0020] In some embodiments, the air permeability of the functional coating is 10 to 75 s / 100 cc.

[0021] In some embodiments, the ionic conductivity of the composite membrane is 0.62 to 0.98 mS / cm.

[0022] In some embodiments, the thickness of the first substrate layer and the second substrate layer are independently 2 to 20 μm.

[0023] In some embodiments, the first substrate layer and the second substrate layer each independently include PP and / or PE.

[0024] The method for preparing the composite diaphragm as described above comprises the following steps:

[0025] A mixed slurry of a two-dimensional sheet material dispersion and a polydopamine lithium salt dispersion is coated on the surface of the first substrate layer to form a first coating body, and the first coating body is bonded to the second substrate layer and then subjected to a shaping treatment to obtain the composite diaphragm.

[0026] In some embodiments, the method for preparing the two-dimensional sheet material dispersion specifically includes: ultrasonically crushing a mixture of the two-dimensional sheet material and the first solvent, removing undispersed floating matter, and obtaining the two-dimensional sheet material dispersion.

[0027] In some embodiments, the method for preparing a polydopamine lithium salt dispersion specifically includes: mixing dopamine and a second solvent, and using a lithium source to adjust the pH of the mixed system to 7.5 to 8.5.

[0028] In some implementations, the two-dimensional sheet material dispersion is 250 to 1100 parts by mass, and the polydopamine lithium salt dispersion is 25 to 110 parts by mass.

[0029] In some implementations, the mixed slurry further includes a thickener, and the thickener is 0.1 to 3 parts by mass.

[0030] In terms of weight, the two-dimensional sheet material is 25 to 95 parts, and the first solvent is 900 to 1000 parts.

[0031] In some embodiments, during the ultrasonic fragmentation process, the temperature of the mixture is controlled to be 20-30°C.

[0032] In some implementations, the dopamine is 2 to 5 parts by mass, and the second solvent is 90 to 100 parts by mass.

[0033] In some embodiments, the shaping treatment includes drying and hot rolling.

[0034] A battery comprises the composite diaphragm or the composite diaphragm obtained by the method.

[0035] An electrical device comprises the battery.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) In the composite diaphragm of the present invention, the intermediate functional coating is stacked by two-dimensional sheet materials, and the distance between the sheets is regulated by the lithium ions doped therein; the two-dimensional sheet materials form a strong network structure through hydrogen bonding, which enhances the overall strength of the composite diaphragm, has high electrical conductivity and long service life; during the charge and discharge cycle, the distance between the sheets can effectively block large-particle transition metals such as Mn; and the intermediate functional coating is fixed by the substrates on both sides, which not only avoids direct contact with the positive and negative active materials, but also reduces the risk of escaping into the electrolyte.

[0038] (2) The preparation method of the composite diaphragm of the present invention is simple and easy. Through the coordination of various steps, a composite diaphragm with high needle puncture strength, high electrical conductivity and excellent comprehensive performance is obtained.

[0039] (3) The battery of the present invention has excellent capacity retention, good cycle stability, low Mn enrichment rate at the negative terminal, and good safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 It is a schematic diagram of the structure of the composite diaphragm of the present invention;

[0042] Figure 2 is a scanning electron microscope image of a cross section of the composite diaphragm of the present invention;

[0043] Figure 3 is the X-ray diffraction pattern of the functional coating of the present invention.

[0044] Reference numerals:

[0045] 1-first substrate layer, 2-second substrate layer, 3-functional coating, 301-two-dimensional sheet material. DETAILED DESCRIPTION

[0046] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0047] According to one aspect of the present invention, the present invention relates to a composite diaphragm, comprising a first substrate layer, a functional coating and a second substrate layer, wherein the functional coating is located between the first substrate layer and the second substrate layer; the functional coating comprises a two-dimensional sheet material and polydopamine lithium salt.

[0048] In the composite diaphragm of the present invention, the intermediate functional coating is stacked by two-dimensional sheet materials, and the distance between the sheets is regulated by the lithium ions doped therein; the two-dimensional sheet materials form a strong network structure through hydrogen bonding, which enhances the overall strength of the composite diaphragm, has high electrical conductivity and long service life; during the charge and discharge cycle, the distance between the sheets can effectively block large-particle transition metals such as Mn; and the intermediate functional coating is fixed by the substrates on both sides, which not only avoids direct contact with the positive and negative active materials, but also reduces the risk of escaping into the electrolyte.

[0049] In some embodiments, the functional coating of the present invention is in a continuous full coating state.

[0050] In some embodiments, along the thickness direction of the functional coating, the two-dimensional sheet material is in a stacked form, the lithium element is mainly filled between the two-dimensional sheet materials, and part of the polydopamine is located between the functional coating and the first substrate layer or the second substrate layer. Along the thickness direction of the functional coating, the spacing d between any adjacent two-dimensional sheet materials satisfies: 0.7nm≤d≤1.4nm, for example, 0.7nm, 0.8nm, 0.9nm, 1nm, 1.1nm, 1.2nm, 1.3nm, 1.4nm, etc., or any range value between the two. The spacing between any adjacent two-dimensional sheet materials in the present application is suitable, which is more conducive to improving the overall strength of the composite diaphragm.

[0051] In some embodiments, the length of the two-dimensional sheet material is 0.1 to 5 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc., or any range between two values.

[0052] In some embodiments, in the functional coating, the mass content A of the two-dimensional sheet material satisfies: A ≥ 85%, for example 85% to 96%, for example 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, etc.; the mass content B of the polydopamine lithium salt satisfies: B ≥ 3%, flowing into 3% to 14%, for example 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 14%, etc.

[0053] In some embodiments, the two-dimensional sheet material includes a combination of one or more of graphene oxide, graphene, amino-modified graphene oxide, MXene and molybdenum disulfide, such as a combination of graphene oxide and graphene, a combination of amino-modified graphene oxide and MXene, a combination of MXene and molybdenum disulfide, etc. It should be noted that MXene is a two-dimensional material well known to those skilled in the art, including a substance composed of a carbide, a nitride or a carbonitride of a transition metal. In some embodiments, the MXene material is Ti 3 AlC 2 .

[0054] In some embodiments, the functional coating also includes a thickener, and the mass content C of the thickener satisfies: C ≥ 0.3%, for example, 0.3% to 1.5%, for example, 0.3%, 0.5%, 1%, 1.5%, etc., and A+B+C = 100%; the thickener includes one or more of carboxymethyl cellulose, carboxyethyl cellulose, guar gum, polyethylene oxide, pine oil, polyvinyl alcohol, polyacrylic acid and polyurethane.

[0055] In some embodiments, the thickness of the functional coating is 0.4 to 10 μm, including but not limited to 0.4 μm, 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc. The present invention uses a functional coating of appropriate thickness, which is more conducive to ensuring the overall strength and conductivity of the composite diaphragm and improving the overall performance.

[0056] In some embodiments, the composite membrane has a needle puncture strength of 350-900 gf, such as 500 gf, 600 gf, 700 gf, 800 gf, 900 gf, etc. The functional coating has a needle puncture strength of 60-300 gf, such as 100 gf, 150 gf, 200 gf, 250 gf, 300 gf, etc.

[0057] In some embodiments, the bonding strength between the first substrate layer and the second substrate layer is greater than 10 N / m, such as 10.5 N / m, 11 N / m, 12 N / m, 13 N / m, 15 N / m, etc. In the composite diaphragm of the present invention, the first substrate layer and the second substrate layer have high bonding strength, that is, the bonding performance of each layer of the composite diaphragm is good.

[0058] In some embodiments, the air permeability of the functional coating is 10-75 s / 100 cc, such as 10 s / 100 cc, 20 s / 100 cc, 30 s / 100 cc, 40 s / 100 cc, etc. The functional coating of the present invention has suitable air permeability.

[0059] In some embodiments, the ionic conductivity of the composite membrane is 0.62-0.98 mS / cm, such as 0.62 mS / cm, 0.7 mS / cm, 0.75 mS / cm, 0.8 mS / cm, 0.9 mS / cm, etc. The composite membrane of the present invention has high ionic conductivity.

[0060] In some embodiments, the thickness of the first substrate layer and the second substrate layer is independently 2 to 20 μm, such as 2 μm, 3 μm, 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, etc. The first substrate layer and the second substrate layer are independently composed of PP (polypropylene) and / or PE (polyethylene).

[0061] According to another aspect of the present invention, the present invention also relates to a method for preparing the composite diaphragm as described above, comprising the following steps:

[0062] A mixed slurry formed by a two-dimensional sheet material dispersion and a polydopamine lithium salt dispersion is applied to the surface of the first substrate layer to form a first coating body, and the mixed slurry layer of the first coating body is bonded to the second substrate layer and then subjected to a shaping treatment to obtain the composite diaphragm.

[0063] The preparation method of the composite diaphragm of the present invention is simple and easy, and a composite diaphragm with high needle puncture strength, high electrical conductivity and excellent comprehensive performance can be obtained through the coordination of various steps.

[0064] In some embodiments, the method for preparing the two-dimensional sheet material dispersion specifically includes: subjecting a mixture of the two-dimensional sheet material and the first solvent to ultrasonic crushing, during which the temperature of the mixture is controlled to be 20-30°C (e.g., 20°C, 25°C, 30°C, etc.); removing undispersed floating objects to obtain a two-dimensional sheet material dispersion; in terms of mass fractions, the two-dimensional sheet material is 25-95 parts (e.g., 25 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts or 90 parts, etc.), and the first solvent is 900-1000 parts (e.g., 900 parts, 950 parts, 1000 parts, etc.). The method disclosed in the present invention can obtain a uniform two-dimensional sheet material dispersion.

[0065] In some embodiments, the preparation method of the polydopamine lithium salt dispersion specifically includes: mixing dopamine and a second solvent, and using a lithium source to adjust the pH of the mixed system to 7.5-8.5 (for example, 7.5, 8 or 8.5, etc.); in terms of mass fractions, the dopamine is 2-5 parts (for example, 2 parts, 3 parts, 4 parts or 5 parts, etc.), and the second solvent is 90-100 parts (for example, 90 parts, 95 parts or 100 parts, etc.).

[0066] In some embodiments, the two-dimensional sheet material dispersion is 250 to 1100 parts by mass, such as 250 parts, 300 parts, 500 parts, 600 parts, 700 parts, 900 parts, 950 parts, 1000 parts or 1100 parts, etc. The polydopamine lithium salt dispersion is 25 to 110 parts, such as 25 parts, 40 parts, 50 parts, 60 parts, 80 parts, 90 parts, 100 parts or 110 parts, etc. The two-dimensional sheet material dispersion and the polydopamine lithium salt dispersion adopt a suitable mass ratio so that the two-dimensional sheet material and the polydopamine lithium salt in the final functional coating have a suitable ratio to coordinate and improve the strength and other properties of the composite diaphragm.

[0067] In some embodiments, the mixed slurry further includes a thickener, and the thickener is 0.1 to 3 parts by mass, for example, 0.1 parts, 0.3 parts, 0.5 parts, 1 parts, 2 parts or 3 parts.

[0068] In some embodiments, the shaping process comprises drying and hot rolling performed sequentially.

[0069] In some embodiments, the first solvent and the second solvent each independently include water, such as deionized water.

[0070] According to another aspect of the present invention, the present invention also relates to a battery, comprising the composite diaphragm described above, or the composite diaphragm obtained by the described method.

[0071] The battery of the present invention has excellent capacity retention rate, good cycle stability, low Mn enrichment rate at the negative terminal and good safety performance.

[0072] According to another aspect of the present invention, the present invention also relates to an electric device, comprising the battery, wherein the electric device includes a portable device, an electric car, an electric tool, and the like.

[0073] The following is further explained in conjunction with specific embodiments and comparative examples.

[0074] Example 1

[0075] A composite diaphragm, such as Figure 1 As shown, it includes a first substrate layer 1, a functional coating 3 and a second substrate layer 2, wherein the functional coating 3 is located between the first substrate layer 1 and the second substrate layer 2; the functional coating 3 contains a two-dimensional sheet material 301 and polydopamine lithium salt (not shown). Figure 1 The d in the figure represents the distance between any adjacent two-dimensional sheet materials along the thickness direction of the functional coating. Figure 2 shown.

[0076] A method for preparing a composite diaphragm comprises the following steps:

[0077] (1) Preparation of a two-dimensional sheet material dispersion: 50 parts of graphene oxide were added to 950 parts of deionized water, the temperature was maintained at 25°C, ultrasonically crushed and dispersed using a cell crusher, and undispersed floating matter was removed using a filter to make the size distribution of the obtained two-dimensional sheets between 400 and 1000 nm, thereby obtaining a two-dimensional sheet material dispersion.

[0078] (2) Preparation of polydopamine lithium salt dispersion: 3 parts of polydopamine were dissolved in 97 parts of deionized water, and the pH was adjusted to 8.2 with LiOH to obtain a polydopamine lithium salt dispersion.

[0079] (3) Take 1000 parts of two-dimensional sheet material dispersion, 0.4 parts of carboxymethyl cellulose and 100 parts of polydopamine lithium salt dispersion, stir evenly to obtain a mixed slurry, use micro-gravure coating technology to coat the mixed slurry on the first substrate layer 1, and before the mixed slurry is dry, compound the second substrate layer 2 onto the mixed slurry, dry, and heat roller pressure to shape, to obtain a composite diaphragm with a functional coating 3 with a thickness of 2.8 μm.

[0080] Example 2

[0081] A method for preparing a composite diaphragm, which differs from Example 1 in that:

[0082] In step (1), 25 parts of graphene oxide are added to 975 parts of deionized water.

[0083] A composite diaphragm with a functional coating 3 thickness of 1.6 μm was obtained.

[0084] Example 3

[0085] A method for preparing a composite diaphragm, which differs from Example 1 in that:

[0086] In step (1), 90 parts of graphene oxide are added to 910 parts of deionized water.

[0087] A composite diaphragm with a functional coating 3 thickness of 4.6 μm was obtained.

[0088] Example 4

[0089] A method for preparing a composite diaphragm, which differs from Example 1 in that:

[0090] In step (3), 250 parts of two-dimensional sheet material dispersion, 0.1 parts of carboxymethyl cellulose and 25 parts of polydopamine lithium salt dispersion are taken and stirred evenly to obtain a mixed slurry. The mixed slurry is coated on the first substrate layer using micro-gravure coating technology. Before the mixed slurry dries, the second substrate layer is compounded to the mixed slurry, dried, and hot roller pressure-shaped to obtain a composite diaphragm with a functional coating 3 thickness of 1.4 μm.

[0091] Example 5

[0092] A method for preparing a composite diaphragm, which differs from Example 1 in that:

[0093] In step (3), the micro-gravure coating technology is adjusted to obtain a composite diaphragm with a functional coating 3 thickness of 0.6 μm.

[0094] Example 6

[0095] A method for preparing a composite diaphragm, which differs from Example 1 in that:

[0096] In step (3), the micro-gravure coating technology is adjusted to obtain a composite diaphragm with a functional coating 3 thickness of 8.0 μm.

[0097] Example 7

[0098] A method for preparing a composite diaphragm, which differs from Example 1 in that:

[0099] The two-dimensional sheet material in step (1) is amino-treated graphene oxide.

[0100] Example 8

[0101] A method for preparing a composite diaphragm, which differs from Example 1 in that:

[0102] The two-dimensional sheet material in step (1) is MXene.

[0103] Comparative Example 1

[0104] A method for preparing a composite diaphragm comprises the following steps:

[0105] (1) Preparation of polydopamine lithium salt dispersion: 3 parts of polydopamine were dissolved in 97 parts of deionized water, and the pH was adjusted to 7.5-8.5 with LiOH to obtain a polydopamine lithium salt dispersion.

[0106] (2) Take 50 parts of aluminum oxide (particle size distribution is 400-1000 μm), 0.4 parts of carboxymethyl cellulose, 100 parts of polydopamine lithium salt dispersion and 950 parts of deionized water, stir evenly, use micro-gravure coating technology to coat the mixed slurry (dispersion) on the substrate diaphragm, and before the mixed slurry dries, composite another substrate diaphragm onto the mixed slurry, dry, and heat roller pressure to shape, to obtain a composite diaphragm with a functional coating thickness of 2.8 μm.

[0107] Comparative Example 2

[0108] A method for preparing a composite diaphragm comprises the following steps:

[0109] Steps (1) and (2) are the same as those in Example 1.

[0110] (3) 1000 parts of two-dimensional sheet material dispersion, 0.4 parts of carboxymethyl cellulose and 100 parts of polydopamine lithium salt dispersion are taken and stirred evenly to obtain a mixed slurry. The mixed slurry is coated on the first substrate layer using micro-gravure coating technology, dried, and hot roller pressure is used for shaping to obtain a composite diaphragm with a functional coating thickness of 2.8 μm.

[0111] Comparative Example 3

[0112] A method for preparing a composite diaphragm comprises the following steps:

[0113] (1) Preparation of a two-dimensional sheet material dispersion: 50 parts of graphene oxide were added to 950 parts of deionized water, the temperature was maintained at 25°C, ultrasonically crushed and dispersed using a cell crusher, and undispersed floating matter was removed using a filter to make the size distribution of the obtained two-dimensional sheets between 400 and 1000 nm, thereby obtaining a two-dimensional sheet material dispersion.

[0114] (2) 1000 parts of the two-dimensional sheet material dispersion and 0.4 parts of carboxymethyl cellulose were mixed and stirred evenly to obtain a mixed slurry. The mixed slurry was coated on the first substrate layer using a micro-gravure coating technique. Before the mixed slurry was dry, the second substrate layer was composited onto the mixed slurry, dried, and formed by hot roller pressure to obtain a composite diaphragm with a functional coating thickness of 2.8 μm.

[0115] Test example

[0116] The composite diaphragms obtained in the examples and comparative examples and the corresponding batteries were subjected to performance tests as follows:

[0117] 1. Coating air permeability

[0118] Permeability refers to the time required for 100 ml of gas to pass through a membrane of fixed area. Permeability growth value = composite membrane permeability - all substrate permeability.

[0119] 2. Coating thickness test

[0120] Using CP-SEM technology, 6 locations were randomly sampled from each group of diaphragms, the coating thickness was recorded, and the average value was taken.

[0121] 3. Test of distance d between coating layers

[0122] The top or bottom substrate is peeled off, so that one side of the coating is exposed to the air, and baked at 80°C for half an hour. The interlayer spacing is detected using a Rigaku Ultima IV polycrystalline X-ray diffractometer with a scanning range of 5° to 50°. According to the formula d = λ / (2sinθ), the interlayer distance d can be calculated; where λ = 0.154nm. The X-ray diffraction pattern of the functional coating is shown in Figure 3 shown.

[0123] 4. Composite diaphragm needle puncture strength and coating needle puncture strength test

[0124] Composite diaphragm needle puncture strength test: Use a tensile testing machine (RZ-DW100) to test, the diaphragm sample is 80mm×80mm, and the descending speed is 120mm / min. Test 10 groups of values ​​and take the average value.

[0125] Coating needle puncture strength test: coating needle puncture strength = composite diaphragm needle puncture strength - all substrate base material strength.

[0126] 5. Bonding strength between the first substrate layer and the second substrate layer

[0127] The test was conducted using a tensile testing machine (RZ-DW100). The membrane was cut into 3cm*10cm strips and peeled off at 180° along the long side at a speed of 50mm / min. Six sets of values ​​were tested and the average value was taken.

[0128] 6. Ionic conductivity performance

[0129] In an argon glove box, the membrane was made into a 2016 button battery, and an appropriate amount of electrolyte (EC:PC:DEC = 1:3:1, 0.5 Mol / L LiPF6) was added. The AC impedance test in the electrochemical workstation showed that σ = L / (Rb*A), where σ is the ionic conductivity (mS / cm); L is the thickness of the membrane (cm); Rb is the intrinsic resistance of the membrane (Ω); A is the effective area (cm 2 ).

[0130] 7. Capacity retention rate

[0131] The coated diaphragm, lithium iron phosphate positive electrode sheet and graphite negative electrode sheet are wound into a soft-package lithium-ion battery. The battery is cycled 300 times at 0.3C charge and discharge, and the capacity before and after the cycle is tested. The capacity retention rate = capacity after cycle / capacity before cycle.

[0132] 8. Mn enrichment rate at the negative end

[0133] The coated diaphragm and the lithium iron phosphate positive electrode sheet and the graphite negative electrode sheet are wound to form a soft-package lithium-ion battery, and the battery is cycled 300 times at 0.3C charge and discharge. The battery after the cycle is disassembled, the quantitative negative electrode active material is digested and fixed with aqua regia, and the Mn content in the digestion solution is detected with an ICP instrument. Among them, the manganese content of the negative electrode active material in Comparative Example 1 is recorded as 100%, and the Mn enrichment rate of the corresponding negative electrode active material is calculated.

[0134] The test results are shown in Table 1.

[0135] Table 1 Test results

[0136]

[0137]

[0138] It can be seen from Table 1 that the composite diaphragm obtained by the method of each embodiment of the present invention has excellent needle puncture strength, suitable air permeability, high bonding strength between the first substrate layer and the second substrate layer, and high ionic conductivity; the capacity retention rate of the battery obtained by the composite diaphragm of each embodiment is high, which is above 88%, and the Mn enrichment rate at the negative terminal is low, which is below 11%.

[0139] The coating of the composite diaphragm obtained by the method of Comparative Example 1 has low needle puncture strength, low bonding strength between the two substrates, low capacity retention rate of the obtained battery, and extremely high Mn enrichment rate at the negative terminal.

[0140] The composite diaphragm obtained by the method of Comparative Example 2 has low puncture strength, a low capacity retention rate of the obtained battery, and a high Mn enrichment rate at the negative terminal.

[0141] The bonding strength between the two substrates of the composite diaphragm obtained by the method of Comparative Example 3 is low, the ion conductivity is reduced, and the capacity retention rate of the obtained battery is low.

[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite diaphragm, characterized in that: It comprises a first substrate layer, a functional coating layer and a second substrate layer, wherein the functional coating layer is located between the first substrate layer and the second substrate layer; The functional coating comprises a two-dimensional sheet material and polydopamine lithium salt.

2. The composite diaphragm according to claim 1, characterized in that: Contains at least one of the following features (1) to (6): (1) Along the thickness direction of the functional coating, the two-dimensional sheet material is in a stacked form; (2) Along the thickness direction of the functional coating, the spacing d between any adjacent two-dimensional sheet materials satisfies: 0.7 nm ≤ d ≤ 1.4 nm; (3) In the functional coating, the mass content A of the two-dimensional sheet material satisfies: A ≥ 85%, and the mass content B of the polydopamine lithium salt satisfies: B ≥ 3%; (4) The two-dimensional sheet material includes at least one of graphene oxide, graphene, amino-modified graphene oxide, Mxene and molybdenum disulfide; (5) The length of the two-dimensional sheet material is 0.1 to 5 μm; (6) The thickness of the functional coating is 0.4 to 10 μm.

3. The composite diaphragm according to claim 1, characterized in that: Contains at least one of the following features (1) to (2): (1) The functional coating further comprises a thickener, and the mass content C of the thickener satisfies: C ≥ 0.3%, and A + B + C = 100%; (2) The functional coating further comprises a thickener, wherein the thickener comprises at least one of carboxymethyl cellulose, carboxyethyl cellulose, guar gum, polyethylene oxide, pinene alcohol, polyvinyl alcohol, polyacrylic acid and polyurethane.

4. The composite diaphragm according to claim 1, characterized in that: Contains at least one of the following features (1) to (6): (1) The composite membrane has a needle puncture strength of 350 to 900 gf, and the functional coating has a needle puncture strength of 60 to 300 gf; (2) The bonding strength between the first substrate layer and the second substrate layer is greater than 10 N / m; (3) The air permeability of the functional coating is 10 to 75 s / 100 cc; (4) The ionic conductivity of the composite membrane is 0.62 to 0.98 mS / cm; (5) The thickness of the first substrate layer and the second substrate layer are each independently 2 to 20 μm; (6) The first substrate layer and the second substrate layer each independently include PP and / or PE.

5. The method for preparing a composite diaphragm according to any one of claims 1 to 4, characterized in that: The following steps are involved: A mixed slurry of a two-dimensional sheet material dispersion and a polydopamine lithium salt dispersion is coated on the surface of the first substrate layer to form a first coating body, and the first coating body is bonded to the second substrate layer and then subjected to a shaping treatment to obtain the composite diaphragm.

6. The method for preparing the composite diaphragm according to claim 5, characterized in that: Contains at least one of the following features (1) to (4): (1) The method for preparing the two-dimensional sheet material dispersion comprises: subjecting a mixture of the two-dimensional sheet material and the first solvent to ultrasonic crushing, removing undispersed floating matter, and obtaining the two-dimensional sheet material dispersion; (2) A method for preparing a polydopamine lithium salt dispersion, specifically comprising: mixing dopamine and a second solvent, and using a lithium source to adjust the pH of the mixed system to 7.5 to 8.5; (3) In terms of weight, the two-dimensional sheet material dispersion is 250 to 1100 parts, and the polydopamine lithium salt dispersion is 25 to 110 parts; (4) The mixed slurry also includes a thickener, and the thickener is 0.1 to 3 parts by mass.

7. The method for preparing a composite diaphragm according to claim 6, characterized in that: Contains at least one of the following features (1) to (3): (1) In terms of weight, the two-dimensional sheet material is 25 to 95 parts, and the first solvent is 900 to 1000 parts; (2) During the ultrasonic crushing process, the temperature of the mixture is controlled to be 20 to 30° C.; (3) In terms of weight, the dopamine is 2 to 5 parts, and the second solvent is 90 to 100 parts.

8. The method for preparing a composite diaphragm according to claim 5, characterized in that: The setting treatment includes drying and hot rolling.

9. A battery, characterized in that: The invention comprises the composite diaphragm according to any one of claims 1 to 4, or the composite diaphragm obtained by the method according to any one of claims 5 to 8.

10. An electrical device, characterized in that: A battery comprising the battery of claim 9.

Citation Information

Cited By

  • Protective layer, sodium ion battery, power utilization device and preparation method of protective layer

    CN121439929A